2020
DOI: 10.1111/os.12781
|View full text |Cite
|
Sign up to set email alerts
|

Early Follow‐Up of Arthroscopic Latarjet Procedure with Screw or Suture‐Button Fixation for Recurrent Anterior Shoulder Instability

Abstract: Objective To evaluate the early clinical and radiographic results of arthroscopic Latarjet procedure using screw or suture‐button fixation in patients with recurrent anterior shoulder dislocation. Methods Twelve patients who underwent arthroscopic Latarjet procedure between January 2015 and December 2018 at our institution were retrospectively studied. Data of the patients' history, including age, gender, side of affected arm, body mass index (BMI), and the number of dislocations since fist dislocation were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 54 publications
(93 reference statements)
1
3
0
Order By: Relevance
“…Although ASES and pain scores of pediatric patients undergoing arthroscopy for instability significantly improved after surgery, ROM remained relatively consistent before and after arthroscopy, similar to outcomes reported for adult patients. 36 , 37 , 38 , 39 The majority of instability patients in this study returned to sport after surgery, at a similar rate to that previously reported of all patients undergoing arthroscopic procedures for instability. 39 , 40 Clinical outcomes for surgical repair of rotator cuff tears in pediatric patients have been reported to be excellent, but these studies have not independently reported outcomes for open and arthroscopic repair.…”
Section: Discussionsupporting
confidence: 82%
“…Although ASES and pain scores of pediatric patients undergoing arthroscopy for instability significantly improved after surgery, ROM remained relatively consistent before and after arthroscopy, similar to outcomes reported for adult patients. 36 , 37 , 38 , 39 The majority of instability patients in this study returned to sport after surgery, at a similar rate to that previously reported of all patients undergoing arthroscopic procedures for instability. 39 , 40 Clinical outcomes for surgical repair of rotator cuff tears in pediatric patients have been reported to be excellent, but these studies have not independently reported outcomes for open and arthroscopic repair.…”
Section: Discussionsupporting
confidence: 82%
“…A further 87 studies were excluded after full‐text review. This left 29 eligible studies [1, 7, 8, 11, 14, 16–18, 23, 24, 29–32, 38, 40–45, 47, 48, 53, 55–59] of which 16 assessed arthroscopic bony Bankart repair, 13 assessed arthroscopic Latarjet (Tables 1 and 2). All studies reported preoperative glenoid bone loss: 21 reported mean preoperative glenoid bone loss, of which 4 created subgroups of glenoid bone loss and reported the mean loss of each subgroup, while 8 used a threshold of glenoid bone loss as a part of their inclusion criteria.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the increased COF shift and bone block motion of more elastic suture-based fixation may actually provide an ability for a lateralized graft to self-correct over time and become flush with the glenoid rim. 12,52,56 Additionally, biological remodeling of the reconstructed glenoid can lead to bone resorption 26,55 as the bony structure readapts toward the native glenoid shape (Wolff law). 22,52,55,58 Whereas screw fixation in these cases results in hardware prominence of the screw heads, causing shoulder pain due to humeral head and subscapular impingement, 11,27,59 the dynamic suture-based techniques have the potential to maintain impingement-free glenohumeral articulation.…”
Section: Discussionmentioning
confidence: 99%